An Efficient Framework Of Identity-based Conditional Privacy-preserving Authentication For Vehicular Ad Hoc Networks - Shareeda, Mahmood Arif Lafta Al (2022)
Vehicular ad hoc networks (VANETs) have become increasingly common in recent years due to their critical role in the field of intelligent transportation by supporting Vehicle-to-Vehicle and Vehicle-to-Infrastructure communications. The security and privacy of VANET are of the utmost importance due to the use of an open wireless communication medium where messages are exchanged in the plain text allowing attackers to intercept, tamper, replay, and delete them. To address these issues, several researcher have been proposed schemes in VANET. The taxonomy of existing schemes is as follows. Public key infrastructure-based conditional privacy-preserving authentication (PKI-CPPA), group signatures-based conditional privacy-preserving authentication (GS-CPPA), and identity-based conditional privacy-preserving authentication (ID-CPPA) schemes. This thesis aims to propose an efficient framework identity-based conditional privacy-preserving authentication (EID-CPPA) based on elliptic curve cryptography to secure communication in VANETs. The proposed EID-CPPA framework comprises four main phases namely System Initialization, Joining, Broadcasting Massages and Updated Parameter. The first phase is System Initialization, where the Trusted Authority (TA) is responsible to generate and preload the public and private keys into each Road-Side Unit (RSU) located on single domain to reduce the size of Certificate Revocation List (CRL)